PENDEKATAN BEHAVIOR DALAM MENANGGULANGI PERILAKU KONSUMTIF PADA SANTRI - Imroatul Maghfiroh; A. Khairuddin; Wawan Juandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
Consumptive lifestyle is a person's lifestyle in meeting the needs of life not in accordance with their needs, but only to fulfill their desires. Consumptive lifestyles occur in many adolescents, including students. Santri who are expected to be able to make social changes among the people, are actually less able to face the consumptive lifestyle which is the impact of globalization. The results show that the behavioral approach can reduce the consumption habits of students. By determining the maximum target of spending every day, raises a sense of caution in the counselee in making purchases. Koneli has also begun to be able to prevent behavior in making purchases based on desire. So that expenses every day the counselee has begun to decrease from the previous habit. In addition, the counselee has also started to save from the remaining money